DELIRIUM PADA LANJUT USIA - Alimudiarnis, Alimudiarnis; Boy Hutaperi (Nusantara Hasana Journal, 2026)
Delirium is an acute neurocognitive syndrome commonly occurring in older adults and is characterized by disturbances in consciousness, attention, cognition, and behavior that develop rapidly and fluctuate throughout the day. This condition is frequently observed among hospitalized elderly patients, particularly those with chronic illnesses, neurological disorders, infections, or those recovering from surgery. Delirium is associated with increased morbidity, mortality, prolonged hospital stays, functional decline, and a higher risk of developing dementia in later life. This review aims to examine the risk factors, pathophysiology, diagnosis, and management of delirium in older adults based on current scientific literature. The method used was a literature review of relevant scientific journals. The findings indicate that the major risk factors for delirium include advanced age, pre-existing cognitive impairment, infection, dehydration, metabolic disturbances, the use of certain medications, and immobility. Diagnosis is established through clinical assessment focusing on acute changes in mental status and impaired attention. Management primarily involves identifying and treating the underlying causes, along with non-pharmacological interventions such as reorientation strategies, early mobilization, sleep optimization, and family support. Pharmacological treatment is reserved for selected cases with severe symptoms that threaten the safety of the patient or others. Early detection and comprehensive management are essential to reduce complications and improve the quality of life of older adults experiencing delirium.